Determinación del contenido de gluten y propiedades reológicas de diferentes variedades de trigo (Triticum aestivum). - Chancusig Pila, Silvia Alexandra (2023)
Wheat is a crop of economic importance due to its relevant nutritional composition such as: proteins, lipids, fiber, minerals (iron, magnesium, zinc, potassium, calcium and phosphorus), besides containing amino acids. The objective of this research was to determine the gluten content and rheological properties of different varieties of wheat (Triticum aestivum). For this purpose, a Fully Loaded Design was used, where Factor C = wheat variety and Factor B = nitrogen levels, with three replications, in addition, physicochemical characteristics and gluten content were analyzed. In terms of moisture, there was no significant difference, while the wet gluten content showed values between 17.4 and 38.89 %; dry gluten results between 8.38 and 15.87 %; gluten strength between 2.20 and 6.00 and protein content between 10.54 and 13.71 %. In relation to the rheological characteristics of the flours obtained from the different varieties of wheat, variety INIAP - COJITAMBO 92 obtained greater absorption of water (66.08), in the development of the dough the time oscillated between 0.63 to 1.89 % in the flour obtained from the varieties INIAP- ZHALAO 2003 and INIAP- VIVAR 2010 respectively. The stability of the samples ranged between 1.97 and 7.34. While, the C2 protein weakening (Nm) obtained similar values, the opposite happened with the C3 starch gelatinization (Nm), C4 starch starch activity (Nm) and C5 starch retrodegradation (Nm), which presented variability in their results.